The illocutionary aspects of linguistic violence and their effects on the subjectivity in J. Butler. - Ponzio, Julia (Rivista Italiana di Filosofia del Linguaggio, 2023)
In Excitable Speech, J. Butler, while privileging a “perlocutionary model” of linguistic violence, at the same time operates a profound critique of the classical concept of the illocutionary act. The illocutionary act understood in its classical sense has to do with a dynamics of constitution. The problematic nature of the phenomenological concept of “constitution” concerns the relationship between body and language, that is, it concerns precisely that relationship that is at the heart of the question of linguistic violence, understood as the capacity of language to act on a body, to injure a body. The rejection of the illocutionary model of the linguistic act is probably determined by the destabilizing effect that Butler’s own redefinition of the concept of the illocutionary act determines. These destabilizing effects have to do with the shift from the plane of the self, or the subject, governed by will and consciousness, to the plane of the “we”, governed, instead, by relations.